NMR studies of phase behaviour in polyacrylonitrile solutions - Golightly, John Anthony (1998)
The aim of the thesis was to study the phase behaviour of aqueous polyacrylonitrile/NaSCN solutions using a variety of nuclear magnetic resonance techniques. Polyacrylonitrile (PAN) is the basis of the acrylic fibre industry, as such fibres contain at least 85% PAN. Despite this industrial importance, the available literature describing the phase behaviour of PAN in solution is far from comprehensive. Bulk 1H NMR relaxation measurements were carried out over a wide range of concentrations and temperatures to probe the molecular dynamics of the PAN and water molecules. Both the T1 and T2 relaxation data was found to be bi-exponential decay for all samples, the relative amplitudes of which were shown to be equal to the ratio of PAN protons to water protons. Both species were found to be in the regime of rapid molecular motion. Bulk 1H NMR self diffusion measurements, using the PFGSTE technique, exhibited a bi-exponential decay of the echo amplitudes. By careful selection of the observation time, Δ, it was possible to independently probe the water and PAN translational diffusion. A background gradient, resulting from inhomogeneities of the magnetic field, complicated the analysis of the data and a novel polynomial least squares fitting procedure was devised to overcome this effect. The measured attenuation of the water diffusion coefficients (D~10-6-10-5 cm²s-1) with increasing PAN volume fraction was modelled according to various theories, including free volume and scaling laws. The study of the PAN diffusion coefficient (D~10-7-10-6 cm²s-1) was limited by the experimental constraints of the NMR spectrometer. A 1H NMR one-dimensional imaging technique was used to study the nonsolvent induced phase separation (coagulation) of a PAN solution. The time dependence of the measured profiles allowed observation of the coagulation process. A diffusion model was developed to fit the experimental data using a semi-infinite diffusion framework. The fitting parameters represented the diffusion coefficients of the water molecules in the solution/ coagulated PAN network, and in the bulk non-solvent/solvent. PAN films were cast at a range of temperatures in non-solvent baths. This was a scaling up of the dimensions of the fibre spinning process and was used to investigate the range of morphologies which can be formed in the wet-spinning of acrylic fibres. Before any drying processes, water molecules were confined in the porous structure of the saturated films, and their NMR relaxation and self diffusion behaviour was investigated. Parameters describing the pore size and the tortuosity were derived from these studies and scanning electron microscopy was used as a comparative technique. The pore sizes predicted from the NMR data span a smaller spatial range than those observed from SEM. This is explained by the fundamental differences between the two techniques.